1992
DOI: 10.1007/bf02550119
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral and contralateral testicular blood flows during unilateral testicular torsion by133Xe clearance technique

Abstract: Testicular blood flows during unilateral testicular torsion were measured by Xenon-133 clearance technique. Xenon-133 was injected via the left carotid artery into the heart. Measurements were performed in control and left-sided testicular torsion groups, each consisting of ten rats. Left and right testicular blood flows, which were 29.157 +/- 2.272 ml/100 g/min and 29.773 +/- 2.934 ml/100 g/min in the controls, were 11.983 +/- 3.655 ml/100 g/min and 16.098 +/- 3.757 ml/100 g/min in the experimental group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 17 publications
3
18
0
1
Order By: Relevance
“…An afferent stimulus from the twisted testis has been suggested to initiate a reflex decrease in the contralateral testicular blood flow, and a prolonged low perfusion state has been suggested to be the main mechanism of deterioration. Subsequently experimental studies have supported the decrease in the contralateral testicular blood flow [16, 17]. The 47% decrease in contralateral testicular blood flow after 180 min of torsion in the present experimental design has also confirmed previous studies.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…An afferent stimulus from the twisted testis has been suggested to initiate a reflex decrease in the contralateral testicular blood flow, and a prolonged low perfusion state has been suggested to be the main mechanism of deterioration. Subsequently experimental studies have supported the decrease in the contralateral testicular blood flow [16, 17]. The 47% decrease in contralateral testicular blood flow after 180 min of torsion in the present experimental design has also confirmed previous studies.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, 1 h of torsion would be an inadequate interval for the required decrease in blood flow to be manifested through decreased intratesticular pO 2 values. On the other hand, it is known that ipsilateral testicular torsion is followed by an immediate decrease in contralateral testicular blood flow [15, 16, 17]. In the present experimental design, not only the blood flow, but also the relative oxygen contents have been found to be decreased within 1 h of ipsilateral torsion.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It has been reported that unilateral testicular torsion produces a reduction of blood ow in the non-twisted testis, which gradually increases after the detorsion procedure (Tanyel et al 1989, Kizilcan et al 1992 and involves the generation of toxic reactive oxygen species (for example, hydrogen peroxide, hydroxyl radical, superoxide anion) that may damage several cellular components by peroxidation of cell membrane lipids (Akgür et al 1994a). Experimental studies have revealed that unilateral testicular torsion results in an increase in lipid peroxidation products such as lactic acid, hypoxanthine and thiobarbituric acid reactive products in the contralateral untwisted testis (Akgür et al 1994a, Saba et al 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Tek taraflı testis torsiyonu sonrası her iki testiküler arterde azalan kan akımının uzun dönem sonuçları testis fonksiyonu ve fertiliteyi etkilemektedir [19,20]. Nagler [21], Saba [15], Tanyel [22], Cerasara [23] ve Krarup [24] karşı testisin tek taraflı testis torsiyonundan etkilendiğini, buna karşın Becker ile Turner [25], Turner [26], Akgür [27,28] ve Gürdal [29] ise bu işlemin karşı testiste bir değişime yol açmadığını belirtmişlerdir.…”
Section: Discussionunclassified